PROPERTIES OF THE QUANTUM WIRES GROWN ON V-GROOVED AL0.3GA0.7AS/GAAS SUBSTRATE BY ATMOSPHERIC-PRESSURE METALORGANIC CHEMICAL-VAPOR-DEPOSITION - LEE, MS; KIM, Y; KIM, MS; KIM, SI; MIN, SK; KIM, YD; NAHM, S (AMER INST PHYSICS, 1993)
We report the successful growth of quantum wire (QWR) structures of AlxGa1-xAs/GaAs/AlxGa1-xAs on a V-grooved Al0.3Ga0.7As/GaAs substrate. The samples are studied by photoluminescence spectra. The structures are grown by atmospheric pressure metalorganic chemical vapor deposition (MOCVD). The GaAs QWRs are fabricated on a V-grooved Al0.3Ga0.7As/GaAs substrate instead of GaAs substrate. Due to the effect of the Al0.3Ga0.7As layer, a necking area is formed in the side quantum wells (QWLs) near the bottom of the V groove. This results in a reduction of the lateral widths of the QWRs. Also, the luminescence of the QWRs is greatly enhanced in spite of low packing density. It is the first structure made in attempts to produce the quantum-size effects on a V-grooved substrate with non-(111) facets.
Keywords: OPTICAL-PROPERTIES; CARRIER CAPTURE; LASERS; GAAS; CONFINEMENT; OMCVD